PEMANFAATAN BAHAN PEWARNA ALAM SEBAGAI ALTERNATIF DALAM PEMBUATAN BATIK TULIS YANG RAMAH LINGKUNGAN - Purwanto _ (PROSIDING SNAST, 2018)
The global issue of environmentally friendly raw materials, processes and products is growing. Utilization of the use of natural staining is one alternative way to produce environmentally friendly products, as well as in the use of natural dyes in batik making. Batik is an original intangible heritage of Indonesia and has been recognized internationally through UNESCO's world organization in 2009 and the city of Yogyakarta has been recognized as the "world batik city" by the Wordl Craft Council (WCC) based on historical value, originality, revitalization and regeneration, economic value, environmentally friendly and has an international reputation. One of the important things is the environment for it is now starting to develop many natural dyes. There are many natural color ingredients such as from tingi tree, jalawe and indigo tree and many others. The purpose of this research is to know the result of natural coloration from tingi tree bark, jalawe and indigo material on cotton batik making material. The method used in this research is to test the extraction process of natural dye materials of indigo leaf (Indigofera), tingi tree bark (Ceriops tagal) and jalawe (Terminalia bellirica), cooking and bleaching auxiliary materials such as caustic soda (NaOH), soda ash (Na2CO3), TRO and hydrogen peroxide (H2O2). The equipment used is scales, buckets, stainless steel pans, stirrers, kenceng, stoves, gloves, scissors and gray scale test equipment. In the staining step the cotton fabric is immersed in the natural dye resulting from the extraction in a cold state. The next step is the fixation process using alum (Al2 (SO4)3.14H2O), lime tohor (CaCO3) and tunjung (FeSO4) done by immersion for 15 minutes with 1:10 concentration ratio, alum fixation (70 g/l), lime (50 g/l) and tunjung (50 g/l), then dipping in the shade or aerated, then analyzed the color of the coloring results of each type of natural dye using a Gray Scale Standard. The results of the study of natural coloring process on cotton fabric through the fixation of alum material produce a color that is younger than its original color, lime fixation changes its color slightly older than its original color and fixation by tunjung changes the direction of the color towards darkness. The combination of lime-alum fixation changes color slightly younger, whereas the mixture of alum-tunjung and lime-tunjung fixation changes the color darker. Then for indigo and jalawe staining with fixation tunjung result dark color toward black, whereas indigo and tinti coloring change color become dark toward dark brown